“„…padł na mnie blady strach i siedziałem jak trusia”.On phraseologisms in the Polish translation of “Dracula” by Magdalena Moltzan-Małkowska - Górna, Agnieszka (Melusine. Old Literature and Culture, 2025)
The article is devoted to the Polish language translation by Magdalena Moltzan-Małkowska of the novel Bram Stoker’s “Dracula”. A special feature of this translation published in 2011 is the high saturation of phraseologisms, the presence of which is a clear feature of the stylistic style of the translation into Polish. The aim of the presented analyses is to show the stylistic consequences of introducing such devices into the translated text (for example, greater expressiveness, changes in emotional marking, and in relation to the creation of characters also modifications in the plane of emotional equivalence) and an attempt to indicate possible motivations for the discussed procedures. What is important for these considerations is the context of the convention of the Gothic novel and the ways in which texts using this convention function in contemporary culture and pop culture.